Identifikasi Potensi Bahaya dengan Metode JSA (Job Safety Analisis) pada Bengkel Las - Cici Aprilliani; Aldri Frinaldi; Dasman Lanin; Rembrandt; Abdi Iswahyudi Yasril; Washilla Audia; Cory Febrina (Poltekkes Kemenkes Semarang, 2025)
Job Safety Analysis (JSA) is a comprehensive risk evaluation and hazard identification system. Its implementation emphasizes the identification of hazards that arise at each stage of the work process. The objective of this study is to identify potential hazards in each work activity so that workers are expected to be able to recognize them. This qualitative study uses a descriptive approach to describe the phenomenon. Respondents were 20 welding workshops in Bukittinggi City. Technical data collection was conducted using Job Safety Analysis (JSA) tables and observations. The study shows that in the Identification of Potential Hazards in Welding Workshops, risk control at the welding workshop stage still presents many potentially hazardous work stages, the most dangerous of which are material cutting, product refining, and painting. The risk assessor obtained still found that stages with high-risk categories were 23%, medium risk categories were 100%, and low risk categories were 76%. The risk control results showed changes in risk levels, with low risk increasing to 100%, medium risk decreasing to 23%, and high risk decreasing to 0%. Welding workshop owners are advised to provide PPE appropriate to the type of work, such as eye protection meeting SNI 3545:2009 standards and heat-resistant gloves. Furthermore, occupational health and safety training should focus on safe welding procedures, handling flammable materials, and evacuation procedures in the event of a fire.